Sustainable science or business as usual? Exploring awareness and actions in German University Laboratories - Caterina Baars; Patrycja Karwasiecka; João Henrique Paulino Pires Eustachio; Andrea Dobri; Jelena Barbir; Sven Kannenberg; Walter Leal Filho (Green Analytical Chemistry, 2025)
As sustainability research covers many disciplines, it is important to understand how sustainable research itself is. Previous studies have shown that laboratories, a core infrastructure of research, consume a large number of resources. However, overall understanding and identification of actions that can improve the current situation is rather unclear due to a large data gap on the opinions and attitudes of staff and students within institutions. This study explored sustainable actions among laboratory staff and students in a sample of German universities, in the categories of materials, devices, procurement, waste disposal, and awareness. For this purpose, a mixed-method approach was applied, consisting of a quantitative survey answered by 81 laboratories, and a qualitative interview conducted within 9 different universities. One of the key findings is that the inclusion of more sustainable laboratory activities (e.g. efficient waste and equipment management) was mostly undertaken by the laboratory staff themselves, which led to many bottom-up approaches. However, the necessary framework from the administration and institutional support is often missing or is rather limited, which hinders progress in existing initiatives and to take advantage of their great potential. To achieve effective change, it is essential to engage all stakeholders in the institution, laboratory personnel, and institutional administrators. The findings provide valuable insights into the landscape of German university laboratories and their actions and highlight potential areas for structural intervention to make the laboratory operations in universities more sustainable.